An Intercenter Comparison of Nasolabial Appearance Including a Center Using Nasoalveolar Molding. (May 2018) - Peanchitlertkajorn, Supakit; Mercado, Ana; Daskalogiannakis, John; Hathaway, Ronald; Russell, Kathleen; Semb, Gunvor; Shaw, William; Lamichane, Manish; Cohen, Marilyn; Long, Ross E.
Objective: To compare nasolabial appearance outcomes of patients with complete unilateral cleft lip and palate (CUCLP) in preadolescence from 4 cleft centers including a center using nasoalveolar molding (NAM) and primary nasal reconstruction. Design: Retrospective cohort study. Setting: Four cleft centers in North America. Patients: 135 subjects with repaired CUCLP. Methods: Frontal and profile facial pictures were assessed using the Asher-McDade rating scale. Intra- and interrater reliability were tested using weighted Kappa statistics. Median scores by center were compared with Kruskal-Wallis statistics. Results: Intrarater reliability scores were moderate to good. Interrater reliability scores were moderate. Significant differences ( P < .05) among centers were found. For nasal form, center G (median = 2.83) had better scores than centers C and D (C median = 3.33, D median = 3.17). For nose symmetry, center G had better scores (median = 2.33) than all other centers (B median = 2.67, C median = 2.83, D median = 2.83). For vermillion border, center G had better scores (median = 2.58) than centers B and C (B median = 3.17, C median = 3.17). For nasolabial profile, center G (median score = 2.67) had better scores than center C (median = 3.00). For total nasolabial score, center G (median = 2.67) had better scores than all other centers (B median = 2.83, C median = 3, D median = 2.83). Conclusion: The protocol followed by center G, the only center that performed NAM and primary nasal reconstruction, produced better results in all categories when compared to center C, the only center that did not perform presurgical orthopedics or lip/nose revisions. When compared to centers that performed traditional presurgical orthopedics and surgical revisions (B and D), center G was not consistently better in all categories. As with other uncontrolled, retrospective intercenter studies, it is not possible to attribute the outcomes to a specific protocol component.